Room-temperature single crystal laser pumped by an electric-discharge HF laser. (September 2016) - Velikanov, S.D.; Dormidonov, A.E.; Zaretsky, N.A.; Kazantsev, S.Yu.; Kozlovsky, V.I.; Kononov, I.G.; Korostelin, Yu.V.; Maneshkin, A.A.; Podmar'kov, Yu.P.; Skasyrsky, Ya.K.; Firsov, K.N.; Frolov, M.P.; et al.
Abstract: A room-temperature laser based on a single crystal has been studied. The crystal was pumped by a nonchain electric-discharge HF laser with a light pulse FWHM of . The pump spot diameter on the crystal surface varied from 3.9 to . The slope efficiency at these values of was 37% – 39 %, respectively. The maximum laser energy was (at ) with the total efficiency with respect to the absorbed pump energy of . A further increase in the laser energy was not achieved because the crystal was destroyed at an incident pump energy and power of and, respectively. The damaged region has a form of a long narrow channel shifted from the entrance surface inside the active element.